2022
DOI: 10.1371/journal.pone.0264433
|View full text |Cite
|
Sign up to set email alerts
|

Contact tracing indicators for COVID-19: Rapid scoping review and conceptual framework

Abstract: Background Contact tracing is one of the key interventions in response to the COVID-19 pandemic but its implementation varies widely across countries. There is little guidance on how to monitor contact tracing performance, and no systematic overview of indicators to assess contact tracing systems or conceptual framework for such indicators exists to date. Methods We conducted a rapid scoping review using a systematic literature search strategy in the peer-reviewed and grey literature as well as open source o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…However, unlike incubation and latency which are estimated based on clinical data, the transmission period isn't easy to measure because it gets affected by control strategies and relies more on observable reports. Based on some works ( Gallo et al., 2020 ; Hu et al., 2020 ; Mee et al., 2022 ; Vogt et al., 2022 ), we assume the average maximum transmission period of most infectious cases to be 12 days, and so we put n = 16 days. Table 1 summarises the information on the periods used.On the other hand, we consider parameters to be distributed according to the mentioned periods above, such that Since the early transmission of latent cases can be neglected ( Liu, Magal, Seydi, & Webb, 2020 ), we assume 0 .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…However, unlike incubation and latency which are estimated based on clinical data, the transmission period isn't easy to measure because it gets affected by control strategies and relies more on observable reports. Based on some works ( Gallo et al., 2020 ; Hu et al., 2020 ; Mee et al., 2022 ; Vogt et al., 2022 ), we assume the average maximum transmission period of most infectious cases to be 12 days, and so we put n = 16 days. Table 1 summarises the information on the periods used.On the other hand, we consider parameters to be distributed according to the mentioned periods above, such that Since the early transmission of latent cases can be neglected ( Liu, Magal, Seydi, & Webb, 2020 ), we assume 0 .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Contact tracing, which includes some sort of quarantine orders, has been implemented by 183 of 187 countries as measured by the Oxford COVID-19 Government Response Tracker [ 36 ]. It is considered to be one of the cornerstones of the response [ 37 ] and is also recommended by the WHO [ 1 ]. Pozo-Martin et al found that there is evidence regarding the incremental effectiveness of both manual and digital contact tracing for COVID-19 epidemic control [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that conceptual frameworks seemed more helpful for understanding surge capacity for healthcare systems as opposed to more upstream public health service delivery (Bonnett et al, 2007 ). Recently, Vogt et al ( 2022 ) published a scoping review of indicators to monitor contact tracing performance and assess contact tracing systems, still noting gaps in input, outcome, and impact indicators. It would be valuable to extend work in this area to consider overarching components and related goals to guide development, planning, and evaluation drawing on different jurisdictions’ experiences with the rapid development (e.g.…”
Section: Discussionmentioning
confidence: 99%